Effect of the composite curing light mode on polymerization shrinkage of resin composites - Diğdem Eren; Feridun Hürmüzlü; Ozden Ozel Bektas (Cumhuriyet University, 2012)
Objectives: The aim of this study was to investigate the effects of light curing method on the polymerization shrinkage of composite resins. Materials and Methods: Eight methods of four different light curing units were tested by forming 16 groups using two different composite types. Resin composite specimens weights were determined with an analytical electronic hydrostatic balance in the air and in water before and after curing. Then specific gravity values were determined. Volumetric polymerization shrinkage was calculated using mathematical formulas. Results: According to the results of this in-vitro study, polymerization shrinkage differed significantly among the light curing units. Conclusions: When the amount of polymerization shrinkage was compared, it was determined that the curing method, which has the greatest total energy density, caused the greatest amount of shrinkage. It was also found out that some of the curing units affected the shrinkage positively in soft-start mode.